2004
DOI: 10.1111/j.1745-4514.2004.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Studies on the Freshness of Rainbow Trout (Oncorhynchus Mykiss Walbaum) Postmortem During Chilled and Frozen Storage

Abstract: Rainbow trout were killed by two methods, asphyxiation and clubbing. The concentration of ATP in specimens of skeletal muscle taken immediately after death was significantly (P<0.01) higher in clubbed (4.41 ± 0.86 μmol/g) than in asphyxiated (2.00 ± 0.69 μmol/g) fish. The shear force (Warner‐Bratzler) required to cut the muscle was higher (P<0.05) in clubbed (8.33 ± 0.61 N) than in asphyxiated (6.85 ± 0.98 N) fish. Changes in the concentration of adenine nucleotides and in shear force were measured at interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…() reported that IMP in crucian carp ( Carassius auratus ) reached a maximum in 4 h postmortem. Similar result was found by Wills & Proctor () in rainbow trout in 3 h stored at 3 °C. Therefore, the value of IMP in AP white muscle we detected on the 2nd day was possibly not the actual maximum attained during chilled storage.…”
Section: Resultssupporting
confidence: 91%
“…() reported that IMP in crucian carp ( Carassius auratus ) reached a maximum in 4 h postmortem. Similar result was found by Wills & Proctor () in rainbow trout in 3 h stored at 3 °C. Therefore, the value of IMP in AP white muscle we detected on the 2nd day was possibly not the actual maximum attained during chilled storage.…”
Section: Resultssupporting
confidence: 91%
“…Fish products provide important components of the human diet (Watterson et al, 2012), but are highly perishable products, as their quality and freshness deteriorate quickly after death (Medina et al, 2009). The results of physical, chemical, and microbiological analysis in addition to sensory evaluations provide the necessary information to measure the quality and freshness of fish muscle (Wills et al, 2004). The current investigation evaluated physical, chemical, and microbiological quality of fillets and mechanically separated meat (MSM) and rated sensory evaluation of fillets of Tilapia that consumed Homeopatila 100 ® .…”
Section: Introductionmentioning
confidence: 99%
“…ATP degradation is one of the most important postmortem biochemical changes in the muscle of fish. The sequence of nucleotide degradation in teleost fish muscle is as follows: ATP -» adenosine diphosphate -» adenosine monophosphate -» IMP -» HxR -> Hx (30). Figure 3A through 3F illustrates the pattern of nucleotide degradation in the muscle of variously brined grass carp fillets stored at 20 and 4°C.…”
Section: Resultsmentioning
confidence: 98%
“…However, for cazon fish muscle (20) and black skipjack muscle (18,20) significantly lower values of ATP were obtained. Factors such as exhaustion, starvation, hunting, and manner of death (20,30) may contribute to the different initial values of ATP. The ATP of CK and Tl rapidly decreased to values lower than 0.1 pmol/g after 48 h of storage at 20°C, whereas T2 decreased to 0.30 pmol/g during the same storage period.…”
Section: Resultsmentioning
confidence: 99%